TECHNOLOGIES OF SPEECH FORMATION IN MENTALLY DEAD CHILDREN 9-13 YEARS OLD - Khovodillayev Murodjon; Kabirova Zarnigor Rakhmonjonovna; G'furova Umida (American Journals, 2023)
Among the leading deviations in the development of speech is a specific disorder of speech acts - the product of speech pronunciation and understanding, in particular, the difficulty of maintaining the complex multi-operational content of speech acts due to the specific characteristics of the operational side of thinking (memory). attention). This is expressed in the absence or incorrect use of indirect linguistic elements both in the process of understanding speech and in the construction of one's own speech.
Keywords: Linguistics, pronunciation, speech, sensor.